Milites Baroli signori e poteri a Barletta tra XII e XIII secolo - Victor Rivera Magos (Regna: Testi e studi su istituzioni, cultura e memoria del Mezzogiorno medievale, 2020)
The Milites Baroli censused in the Catalogus Baronum constitute the beginning of this study on the formation, characteristics and evolution about lordship powers in the Ofanto Valley and particularly in the city of Barletta between the Norman and early Angevin age. Through a focused and complex rereading of the existing documents, the volume analyzes the structure of the Barletta society with particular attention to its military and political élite and to the relationship with central power. Structured during the XII century consequently the intervention of the Norman crown, for the southern sovereigns the milites of Barletta organized and controlled the Ofanto Valley, favoring the unification of the Apulian center with civitas and the bishopric of Canne. Strongly put to the test in the secular relationship with the crown, the élite of the Apulian city is here probed through the study of prosopographic profiles and the pervasiveness of the power used by main local military families. In this point of view, is analyzed both the relationship established from time to time with the ecclesiastical foundations of Outremer and with the Holy Land, and the quality of the intervention in the main places of political and religious power and the characteristics of supremacy. In that sense, particular attention is focused on the dynamics of the conflict, hidden in the city society, as a basic element for understanding the inner workings of power in the local and supralocal context. In this way, the volume is part of the debate on the social and political structure of the cities in the south of Italy and on the aristocratic powers in the Kingdom of Sicily, of which Barletta is a complex and very interesting case.